The Effect of Cat Stretch Exercise on Reducing Menstrual Pain in Female Students - Paryono, Paryono; Rosalina, Rosalina; Wahyuni, Sri; Srimulati, Triwik (Jurnal Kesehatan Metro Sai Wawai, 2024)
Introduction: Dysmenorrhea can reduce school productivity and quality of life in adolescent girls. Cat Stretch exercises can reduce pain but have never been taught to junior high school students at SMP Negeri 1 Gondangrejo Karanganyar. Purpose: The purpose of this research is to determine how giving stretch exercise paint reduces dysmenorrhoea in junior high school students. Method: The type of research used is quantitative with a Quasi-Experimental research design with pretest and posttest with group control. Researchers measured pain at the beginning, then provided intervention for one month and measured dysmenorrhea pain again during the next menstruation. The purposive sampling technique obtained a sample size of 50 junior high school female students, of which 25 were in the intervention group and 25 were in the control group. The data analysis technique used was the Independent T-Test. Results: The average pre-test intensity of menstrual pain in the intervention group was 4.04, decreasing to 2.72 during the post-test. There was a significant difference in students before and after the cat stretching intervention (p=0.000). In contrast, the control group showed an average pain intensity of 3.56 in the pre-test and almost did not decrease during the post-test, namely 3.52 with p=0.327. Testing for pain reduction in the intervention group was 1.32 while the control group was 0.04 with significant difference results (p-value 0.014). Conclusion: Providing cat stretch exercises can reduce dysmenorrhoea pain in female students. Therefore, young women can use stretch paint exercises to reduce dysmenorrhoea non-pharmacologically. Latar Belakang: Dismenorea dapat menurunkan produktivitas sekolah dan kualitas hidup pada remaja putri perempuan. Latihan Cat Stretch dapat menurunkan nyeri namun belum pernah diajakan pada siswa SMP di SMP Negeri 1 Gondangrejo Karanganyar. Penelitian ini bertujuan untuk mengetahui pengaruh dari pemberian cat stretch exercise terhadap pengurangan dismenorea pada siswi SMP Metode: Jenis penelitian yang digunakan kuantitatif dengan rancangan penelitian Quasi Eksperimen dengan pretest posttest with control gruop. Peneliti mengukur nyeri di awal kemudian diberikan intervensi selama satu bulan dan mengukur nyeri dismenore kembali saat menstruasi selanjutnya. Teknik pengambilan sampel purposive sampling, diperoleh jumlah sampel 50 responden siswi Smp, dimana 25 responden kelompok intervensi dan 25 responden kelompok kontrol. Teknik analisa data yang digunakan adalah Independent T Test Hasil: Rata-rata pre test intensitas dismenorea pada kelompok intervensi 4,04 menurun menjadi 2,72 saat posttest. Terdapat perbedaan bermakna pada siswa sebelum dan setelah intervensi cat stretching (p=0,000). Berbeda pada kelompok kontrol yang menunjukkan intensitas nyeri rata- rata pre test 3,56 dan hampir tidak turun saat post test yaitu 3,52 dengan p=0,327. Pengujian penurunan nyeri pada kelompok intervensi 1,32 sedangkan kelompok kontrol 0,04 dengan hasil perbedaan bermakna (p-value 0,014). Simpulan:  Pemberian Latihan cat stretch mampu menurunkan nyeri disminorea pada siswi. Oleh karena itu, remaja putri dapat menjadikan latihan cat stretching sebagai upaya menurunkan disminorea secara nonfarmakologi secara mandiri.